Genomic Identification and Expression Analysis of the Phosphate Transporter Gene Family in Poplar - Zhang, Chunxia; Meng, Sen; Li, Mingjun; Zhao, Zhong (Frontiers in Plant Science, 2016)
Inorganic phosphate is one of key macronutrients essential for plant growth. The acquisition and distribution of phosphate are mediated by phosphate transporters functioning in various physiological and biochemical processes. In the present study, we comprehensively evaluated the phosphate transporter (PHT) gene family in the latest release of the Populus trichocarpa genome (version 3.0; Phytozome 11.0) and a total of 42 PHT genes were identified which formed five clusters: PHT1, PHT2, PHT3, PHT4, and PHO. Among the 42 PHT genes, 41 were localized to 15 Populus chromosomes. Analysis of these genes led to identification of 5-14 transmembrane segments, most of which were conserved within the same cluster. We identified 234 putative cis elements in the 2-kb upstream regions of the 42 PHT genes, many of which are related to development, stress, or hormone. Tissue-specific expression analysis of the 42 PtPHT genes revealed that 25 were highly expressed in the roots of P. tremula, suggesting that most of them might be involved in Pi uptake. Some PtPHT genes were highly expressed in more than six of the twelve investigated tissues of P. tremula, while the expression of a few of them was very low in all investigated tissues. In addition, the expression of the PtPHT genes was verified by quantitative real-time PCR in four tissues of P. simonii. Transcripts of 7 PtPHT genes were detected in all four tested tissues of P. simonii. Most PtPHT genes were expressed in the roots of P. simonii at high levels. Further, PtPHT1.2 and PtPHO9 expression was increased under drought conditions, irrespective of the phosphate levels. In particular, PtPHT1.2 expression was significantly induced by approximately 90-fold. However, the transcriptional changes of some PtPHT genes under drought stress were highly dependent on the phosphate levels. These results will aid in elucidation of the functions of PtPHT in the growth, development, and stress response of the poplar plant.